Rubber growing soils of India: An overview - Joseph M (Rubber Science, 2016)
In India, natural rubber (NR) cultivation is spread in an area of approximately 8.0 lakh hectares and the majority of soils under NR are red ferruginous soils belonging to the Ultisol/Alfisol order containing large proportion of iron and aluminium oxides and hydrous oxides and kaolonite dominated clay. The available literature on physical, chemical and biological properties of the NR growing soils in India, their fertility status and the impact of NR cultivation on soil properties are discussed.. In the traditional NR growing belt, stretching from Kanyakumari district in the south to Dakshina Kannada district in the north, repeated cycles of rubber cultivation in the past one century, increased soil acidity, reduced organic carbon, available K, Ca and Mg contents and led to deficiency of Zn. For the soils int he North-east states of India, there are some indications that NR cultivation improved the organic carbon and available nutrient status compared to shifting cultivation/jhumming practices. Increasing soil reaction to the extremely acidic pH, declining base status and rising deficiency of Zn were reported from the traditional belt as well as from North-East India which warrants further studies and nutrient management strategies to maintain soil health and productivity on a sustainable basis.
Keywords: Hevea brasiliensis; Lateritic soils; Red ferruginous soils; Rubber growing soil; Soil acidity; Soil biology; Soil chemistry; Soil fertility; Soil health